INDICATORS OF COMPLIANCE PRESSURE FOR NURSE IN IMPLEMENTING PROCEDURES : A QUALITATIVE APPROACH - Indah Lestari (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Various rules and regulations applied by hospital management haven't fully warranted nurse compliance in performing standard procedures. Evidence suggests that there was a high level of an adverse event, as phlebitis, infection, and the incidence of risk of falling. The purpose of this research was to find indicators of compliance pressure for nurses in implementing procedur. This study used a phenomenological qualitative study and in-depth interviews were conducted with 20 respondents, taking into account the selection criteria of respondents. Semi-structured questions were delivered to all participants which explored their experience in implementing and complying with procedures. Analyzes thematically, taking into account the results of the field notes. Findings were that Rules and policies, Standard procedures, Communication, Corrections, and confirmations, Accreditation Standards, Professional Standards, Value, and Co-worker support are indicators of compliance pressure for nurses in implementing procedures. It can be concluded that the eight indicators of compliance pressure are appropriate controls and complement the regulatory pillars and normative pillars in building nurse compliance in carrying out procedures.